Moderasi Beragama Sebagai Fondasi Penguatan Indonesia Rukun Dan Damai di Tengah Keberagaman - Fauzan; Maulidya Safira; Intan Elfira; Hairani Hairani; Sarmida Sarmida; Selpita Selpita; Elsa Liana; Aida Rauzhatun; Isna Maya; Wahyu Linda; Mozayani Mozayani (Scientific Journal for Nation Building, 2026)
Indonesia is a pluralistic nation endowed with high ethnic, cultural, and religious diversity. Behind this narrative of harmony, the implementation of religious moderation often remains trapped as a theoretical discourse at the elite level, lacking practical guidelines at the grassroots where social tensions occur. Consequently, a gap persists between macro peace rhetoric and the reality of local sociological interactions. This study aims to bridge this gap by formulating applicable steps to transform the concept of religious moderation into concrete action within a heterogeneous society. The methodology employed is library research, with data collection conducted through a comprehensive review of primary and secondary literature concerning moderation, conflict resolution, and social psychology, which was subsequently examined using content analysis. The principal results indicate that conventional religious moderation strategies are heavily dominated by top-down, normative-legalistic approaches, thereby failing to engage the citizens' emotional aspects. As a solution, this study formulates a harmony-strengthening model based on inclusive dialogue, the utilization of local wisdom, and a practical guide for basic-level conflict resolution. The major conclusion asserts that the internalization of the middle-way values operates effectively and sustainably only when grassroots communities are actively engaged as primary actors rather than mere policy objects. The primary contribution to the field is providing a concrete-conceptual bridge that aligns government macro-regulations with the psychosocial realities of society to achieve robust social integration. Through this humanistic and contextual approach, diversity at the grassroots level can be managed into social capital that reinforces the unity of the Republic of Indonesia.